Centripetal filling and pathological insights: a rare case of sporadic renal hemangioblastoma with literature review - Guo, Lin; Tang, Botao; Chen, Sheng; Jiang, Peng; Zhang, Ting; Liang, Taisheng; Chen, Jibing; Gao, Hongjun (Frontiers in Physiology, 2025)
BackgroundRenal hemangioblastoma (RH) is an uncommon benign tumor primarily found in the central nervous system (CNS), with an exceptionally rare occurrence in the kidney. Its imaging characteristics closely resemble those of malignant tumors, such as renal cell carcinoma (RCC), and its histological features are similar to other hypervascular tumors, including RCC and angiomyolipoma (AML). Consequently, diagnosing RH presents significant challenges. To date, only approximately 31 cases of RH have been reported worldwide, most of which are not associated with Von Hippel-Lindau (VHL) disease. This article presents a case of sporadic RH, supplemented by a comprehensive literature review, with the aim of enhancing the understanding of this condition. The paper will explore its imaging and pathological characteristics, discuss its clinical significance for diagnosis and management, and provide clinicians with valuable insights for differential diagnosis and treatment strategies.Case presentationA 48-year-old male patient was admitted after a routine physical examination revealed a mass in his left kidney. Abdominal computed tomography (CT) showed a solid mass in the upper pole of the left kidney, measuring approximately 6.9 × 5.7 × 5.6 cm with well-defined borders. Contrast-enhanced imaging demonstrated peripheral enhancement of the mass in a “centripetal filling” pattern. Following consultation, we had ultimately performed a nephron-sparing surgery (NSS). Postoperative pathology confirmed sporadic RH. Immunohistochemistry results showed positivity for S-100, inhibin-α, and Neuron-Specific Enolase (NSE), further supporting the diagnosis. During the 9-month postoperative follow-up period, the patient remained free of clinical recurrence.ConclusionThis case report and literature review summarize the clinical features, imaging manifestations, and pathological characteristics of RH. Immunohistochemical markers, including Inhibin-α, S-100, and NSE, are essential for the diagnosis of RH. These markers assist in differentiating RH from other renal tumors, such as RCC and AML, which may present with similar histological features. For patients with minimal symptoms, NSS is the preferred treatment option, as it optimizes renal function preservation and avoids unnecessary overtreatment. This article provides valuable insights for clinicians on the differential diagnosis and treatment strategies for RH, highlighting the importance of a comprehensive evaluation that integrates imaging, pathology, and immunohistochemical findings.